FIGS: spectral fitting constraints on the star formation history of massive galaxies since the cosmic noon - Ferreras, Ignacio; Pasquali, Anna (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We constrain the stellar population properties of a sample of 52 massive galaxies - with stellar mass log (Ms/M⊙) ≳ 10.5 - over the redshift range 0.
Gesehen am 31.05.2019